Microalloyed high-corrosion-resistance iron-based amorphous alloy and preparation method thereof

By using trace alloy elements to replace the rare earth element Y in the iron-based amorphous alloy, a highly corrosion-resistant FeaCobCrcModCeBfM2 amorphous alloy is prepared, which solves the problem of reduced amorphous alloy formation ability after rare earth removal, and simplifies the process and reduces costs. and improve environmental friendliness.

CN119351903APending Publication Date: 2025-01-24XINJIANG UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411481448.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

After removing the rare earth element Y in the existing iron-based amorphous alloy, the amorphous alloy formation ability is significantly reduced, resulting in complex preparation process, high cost and unfriendly to the environment.

Method used

Through micro -alloy adjustment, the micro -alloy element (such as MO, HF, MN, ZR) instead of rare earth element Y, prepare a high -resistant iron -based non -crystal alloy with a chemical formula for the FEACOBCRCMODCEBFM2, and use the vacuum arc melting and casting method to prepare for preparation. Essence

Benefits of technology

It significantly enhances the amorphous state characteristics, mechanical performance, corrosion resistance, and thermal stability of iron -based amorphous alloys, solve the problem of reduced the ability to form the amorphous alloy formation after removal of rare earth, simplify the preparation process, reduce the cost, and reduce the cost, and the cost, and the cost, and the cost, and the cost, and the cost, and the cost, and the cost, and the cost. Improve environmental friendship.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351903A_ABST
    Figure CN119351903A_ABST
Patent Text Reader

Abstract

The invention discloses a microalloyed high-corrosion-resistance iron-based amorphous alloy and a preparation method thereof, the chemical formula is FeaCobCrcModCeBfM2, M is a microalloyed element, specifically one of Mo, Hf, Mn and Zr, and the contents of the elements in the formula are as follows in atomic percent (at.%): a is 41-45, b is 5-9, c is 13-17, d is 10-14, e is 13-17, f is 4-8, and a + b + c + d + e + f = 98; according to the scheme, the trace alloy elements are adopted to replace rare earth elements, by adding the trace alloy elements, the amorphous state characteristic, the mechanical performance, the corrosion resistance and the thermal stability of the iron-based amorphous alloy are remarkably enhanced, theoretical guidance is provided for improving the amorphous forming ability and the performance of the iron-based amorphous alloy in the future, and the application prospect is wide. The rare-earth-free amorphous alloy has wide application prospects in the fields of metal corrosion prevention and amorphous coatings, and the defects that in the prior art, due to negative correlation between rare earth removal and amorphous alloy forming capacity, an amorphous alloy system usually contains rare earth element Y, and then the preparation technology is complex, cost is high and the amorphous alloy is not environmentally friendly are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of amorphous alloy preparation, and in particular relates to a micro-alloyed high-corrosion-resistant iron-based amorphous alloy and a preparation method thereof. Background Art

[0002] Amorphous alloys (also known as metallic glasses) are a new type of metal material. They have long-range disorder, orderly processes, and structural characteristics without common traditional crystal defects (such as dislocations and grain boundaries), which provide amorphous alloys with high thermal stability and excellent physical, mechanical and chemical properties. Amorphous alloys can be divided into Fe-based, Zr-based, Pd-based, etc. according to the main elements. Compared with other materials, Fe-based has more performance advantages, such as higher strength and hardness (strength 3-5GPa, hardness>1000HV), excellent wear and corrosion resistance, and low cost. Therefore, the current research on amorphous alloys has become a hot topic in the field of materials science, and has received widespread attention and application in aerospace, automotive, biomedical and other fields.

[0003] Shen Baolong et al. added 2 at.% Mo to Fe-Mo-Ga-PCB-Si alloy, which increased the glass-forming ability of the alloy to 2.5 mm. The reason for the improvement of amorphous ability is that the addition of a small amount of Mo element inhibits (Fe, Mo) 23 The formation of (B, C)6 phases. Domestic and foreign researchers have studied the effects of Nb, Mn, Y, P and Er on the performance of Fe-Cr amorphous alloys through trace addition methods. Compared with before, the performance of amorphous alloys has been significantly improved in terms of glass forming ability, corrosion resistance and other properties. Through the method of microalloying, the glass forming ability of the alloy can be effectively improved, which effectively hinders the growth of grains. However, some elements play completely different roles in different amorphous alloy systems. Even a small or trace addition may destroy the comprehensive properties of the alloy. For example, adding Nb to Fe 72 -xNbxAl5Ga2P 11 In C6B4 (x=0, 2) amorphous alloy, Nb substitution for Fe does not improve the glass forming ability of the alloy, but reduces the thermal stability of the material. Up to now, the influence of some transition elements on the glass forming ability and performance of Fe-based glass forming ability is still unclear, so a lot of discussion and research is still needed.

[0004] It is reported that one of the most widely used iron-based alloys is the invention patent with patent publication number CN1603445A, which discloses an iron-based bulk amorphous alloy with high glass-forming ability. 48 Cr 15 Mo 14 C 16B6Y2 (SAM1651), because this system contains rare earth element Y, the preparation process becomes more complicated and the cost is high, and it is not environmentally friendly. If the rare earth element Y is removed, the amorphous alloy forming ability of the alloy will be significantly reduced. Therefore, the present invention performs microalloying adjustment on the basis of SAM1651 composition, and it is of great significance to develop an iron-based amorphous alloy with high corrosion resistance. Summary of the invention

[0005] The present invention provides a micro-alloyed high-corrosion-resistant iron-based amorphous alloy and a preparation method thereof. The preparation process of the scheme of the present invention is simple and the cost is low. The obtained iron-based amorphous alloy does not contain rare earth elements (yttrium Y, cerium Ce, etc.), which solves the shortcomings of the prior art that the amorphous alloy system usually contains rare earth element Y due to the negative correlation between de-rare earthing and the ability to form amorphous alloys, thereby causing its preparation process to be complicated and costly.

[0006] The present application provides a micro-alloyed high corrosion resistant iron-based amorphous alloy:

[0007] Its specific chemical formula is FeaCobCrcModCeBfM2, wherein M is a microalloying element, specifically one of Mo, Hf, Mn and Zr, and the content of each element in the formula is expressed in atomic percentage (at.%), as follows: a is 41-45, b is 5-7, c is 13-17, d is 10-14, e is 13-17, f is 4-8, and a+b+c+d+e+f=98.

[0008] As the preferred solution of this application:

[0009] The specific chemical formula of the iron-based amorphous alloy is: FeaCobCrcModCeBfZr2.

[0010] The present invention also provides a method for preparing a micro-alloyed high corrosion-resistant iron-based amorphous alloy, comprising the following steps:

[0011] Step 1, weigh the ingredients according to the chemical formula FeaCobCrcModCeBfM2;

[0012] Step 2: Place the ingredients obtained in step 1 into a vacuum arc melting furnace and adjust the vacuum degree to 5×10 -3 Pa, and argon gas is used as a protective atmosphere, and the argon gas pressure is 0.05MPa; the ingredients are heated and melted, and the alloy ingot is taken out after cooling with the furnace;

[0013] Step 3: Take 1.5-2.5g of the alloy ingot obtained in step 2 and put it into a vacuum arc melting suction casting furnace, and then adjust the vacuum degree to 5×10 -3Pa, argon gas is used as a protective atmosphere, and the argon gas pressure is 0.05 MPa. After the alloy ingot is heated and melted, it is quickly cooled and cast into a shape by suction casting to obtain an amorphous alloy.

[0014] As the preferred solution of this application:

[0015] In step 2, the raw material is heated slowly until it is molten, and then kept in the molten state for 9-11 minutes, and then heated and smelted again, and the heating and smelting are repeated 4-5 times to ensure that an alloy ingot with uniform composition is obtained.

[0016] As the preferred solution of this application:

[0017] In step three, the amorphous alloy is cast into a cylindrical shape with a diameter of 1.4-1.6 mm and a length of ≤40 mm.

[0018] As the preferred solution of this application:

[0019] In step 1, the purity of the raw materials of each ingredient is above 99.5%, and before step 1, the oxide film on the surface of each metal raw material is removed by grinding with coarse sandpaper, then ultrasonic cleaning is performed with industrial alcohol, and finally drying is performed with a hair dryer for standby use.

[0020] Compared with the prior art, the advantages of the present invention include:

[0021] The chemical formula of the micro-alloyed high corrosion-resistant iron-based amorphous alloy prepared by the present invention is FeaCobCrcModCeBfM2, wherein M is any one of the four metals of Mo, Hf, Mn and Zr, that is, trace alloying elements are used to replace rare earth elements in this scheme of the present application. By adding trace alloying elements, the amorphous characteristics, mechanical properties, corrosion resistance and thermal stability of the iron-based amorphous alloy are significantly enhanced, which provides theoretical guidance for improving the amorphous forming ability and performance of iron-based amorphous alloys in the future. At the same time, it has broad application prospects in the field of metal corrosion protection and amorphous coatings, and solves the problem that the prior art usually contains rare earth element Y in the amorphous alloy system due to the negative correlation between de-rare earthing and amorphous alloy forming ability, which leads to the shortcomings of complex preparation process, high cost and environmental unfriendliness. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the XRD diagram of the FeaCobCrcModCeBfM2 bulk amorphous alloy obtained in the example of the present invention.

[0023] Figure 2 This is the DCS diagram of the FeaCobCrcModCeBfM2 bulk amorphous alloy obtained in an example of the present invention.

[0024] Figure 3This is a diagram of the compressive strength and hardness of the FeaCobCrcModCeBfM2 bulk amorphous alloy obtained in an example of the present invention.

[0025] Figure 4 This is the electrochemical polarization curve of the FeaCobCrcModCeBfM2 bulk amorphous alloy obtained in the example of the present invention.

[0026] Figure 5 This is the fracture morphology of the FeaCobCrcModCeBfM2 bulk amorphous alloy after compression obtained in an example of the present invention. DETAILED DESCRIPTION

[0027] The present invention will be further described in detail below in conjunction with specific implementations and with reference to the accompanying drawings. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application.

[0028] Embodiment 1:

[0029] This embodiment provides a microalloyed high corrosion resistant iron-based amorphous alloy, whose chemical formula is

[0030] FeaCobCrcModCeBfM2, wherein M is a microalloying element, specifically one of Mo, Hf, Mn and Zr, that is, the iron-based amorphous alloy provided in this embodiment is any one of the following four types: FeaCobCrcMod +2 CeBf (hereinafter referred to as Mo2), FeaCobCrcModCeBfHf2 (hereinafter referred to as Hf2), FeaCobCrcModCeBfMn2 (hereinafter referred to as Mn2), FeaCobCrcModCeBfZr2 (hereinafter referred to as Zr2);

[0031] The content of each element in the formula is calculated in atomic percentage (at.%), specifically as follows: a is 41-45, b is 5-7, c is 13-17, d is 10-14, e is 13-17, f is 4-8, and a+b+c+d+e+f=98.

[0032] Embodiment 2:

[0033] The present application also provides a method for preparing a micro-alloyed high corrosion-resistant iron-based amorphous alloy.

[0034] The following steps are involved:

[0035] Step 1, weighing ingredients according to the chemical formula FeaCobCrcModCeBfM2, that is, weighing ingredients with Fe, Co, Cr, Mo, C, B or Hf or Mn or Zr as raw materials according to the nominal components in the chemical formula FeaCobCrcModCeBfM2;

[0036] In this step, the purity of the raw materials of each ingredient is above 99.5%, and before this step, the raw materials are first polished with coarse sandpaper to remove the oxide film on the surface of each metal raw material, then ultrasonically cleaned with industrial alcohol, and finally dried with a hair dryer for standby use;

[0037] Step 2: Place the ingredients obtained in step 1 into a vacuum arc melting furnace and adjust the vacuum degree to 5×10 -3 Pa, and argon gas is used as a protective atmosphere, and the argon gas pressure is 0.05MPa; the ingredients are heated and melted, and the alloy ingot is taken out after cooling with the furnace;

[0038] In this step, the raw material is heated by slow heating until it is in a molten state, and then the molten state is maintained for 9-11 minutes, and then the heating and melting holding process is performed again, and the cycle is repeated 4-5 times to ensure that an alloy ingot with uniform composition is obtained; it can be understood that in this embodiment, the specific heating temperature and smelting time should be selected according to actual conditions, and this embodiment is not specifically limited here;

[0039] Step 3: Take 1.5-2.5g of the alloy ingot obtained in step 2 and put it into a vacuum arc melting suction casting furnace, and then adjust the vacuum degree to 5×10 -3 Pa, argon gas is used as a protective atmosphere, and the argon gas pressure is 0.05MPa. After the alloy ingot is heated and melted, it is quickly cooled by suction casting and cast to obtain an amorphous alloy; in this step, the cast shaped amorphous alloy is cylindrical, with a diameter of 1.4-1.6mm and a length of ≤40mm.

[0040] The above three steps are used to obtain four iron-based amorphous alloys of Mo2, Hf2, Mn2, and Zr2 respectively. 12-15 mg samples of the four amorphous alloys are cut for DSC test, and 1 mm (diameter) × 2 mm (height) samples are cut for room temperature compression mechanical properties and hardness performance tests. At the same time, the corrosion resistance of the corresponding samples is tested in 3.5 wt.% NaCl solution. After testing, the performance of the four iron-based amorphous alloys is significantly enhanced.

[0041] Example 3

[0042] Take the iron-based amorphous alloy Mo2 and its preparation method as an example;

[0043] Step (1) Ingredients: According to FeaCobCrcMod +2 The chemical formula of CeBf is that metals Fe, Co, Cr, Mo, C, and B with a purity of more than 99.5% are used as raw materials for weighing and mixing. Before weighing, the oxide film on the surface of each metal raw material is first polished with coarse sandpaper, then ultrasonically cleaned with industrial alcohol, and finally dried with a hair dryer for use;

[0044] Step (2) Vacuum arc furnace smelting: Place the raw materials obtained in step (1) into a vacuum arc melting furnace and adjust the vacuum degree to 5×10 -3 Pa, using argon (pressure 0.05MPa) as a protective atmosphere, slowly heat the alloy until it is completely melted, and keep the melted state for about ten minutes, then perform the heating and melting holding process again, repeat the cycle 4-5 times to ensure the uniformity of the alloy composition; remove the alloy ingot after cooling with the furnace;

[0045] (3) Preparation of bulk amorphous alloy: Take 2 g of the alloy ingot obtained in step (2) and place it in a vacuum arc melting suction casting furnace. Adjust the vacuum degree to 5×10 -3 Pa or less, adjusting the vacuum degree and argon protective atmosphere, and preparing the amorphous alloy sample by copper mold suction casting method, wherein the prepared suction casting sample is cylindrical, with a diameter of 1.5 mm and a length of ≤40 mm;

[0046] (4) Performance testing and results

[0047] The XRD results of Mo2 amorphous alloy with a diameter of 1.5 mm show that all samples exhibit amorphous characteristics, such as Figure 1 As shown, its crystallization temperature is 848K, such as Figure 2 As shown in Table 1, its room temperature compressive mechanical properties and Vickers hardness values ​​are 4854±10GPa and 1278±20HV respectively. 0.3 ,like Figure 2 , 3 As shown in Table 1, the corrosion resistance is significantly improved compared with ordinary stainless steel. Figure 4 As shown in Table 2; it can be seen that the amorphous characteristics, room temperature compression mechanical properties, Vickers hardness and corrosion resistance of the iron-based amorphous alloy Mo2 obtained by the method of the embodiment are significantly enhanced compared with the existing ones. Therefore, the scheme of this embodiment significantly enhances the amorphous characteristics, mechanical properties, corrosion resistance and thermal stability of the iron-based amorphous alloy by replacing rare earth elements with trace alloying elements, which provides theoretical guidance for improving the amorphous forming ability and performance of iron-based amorphous alloys in the future. At the same time, it has broad application prospects in the field of metal corrosion protection and amorphous coatings, and solves the problem that the prior art has a negative correlation between de-rare earthing and amorphous alloy forming ability, resulting in the amorphous alloy system usually containing rare earth element Y, which leads to the shortcomings of complex preparation process, high cost and environmental unfriendliness.

[0048] Embodiment 4:

[0049] Take the iron-based amorphous alloy Hf2 and its preparation method as an example;

[0050] (1) Ingredients: According to the chemical formula of FeaCobCrcModCeBfHf2, metals Fe, Co, Cr, Mo, C, B, and Hf with a purity of more than 99.5% are used as raw materials for weighing and mixing. Before weighing, the oxide film on the surface of each metal raw material is first polished with coarse sandpaper to remove it, then ultrasonically cleaned with industrial alcohol, and finally dried with a hair dryer for use;

[0051] (2) Vacuum arc furnace melting: The raw materials obtained in step (1) are placed in a vacuum arc melting furnace and the vacuum degree is adjusted to 5×10 -3 Pa, using argon (pressure 0.05MPa) as a protective atmosphere, slowly heat the alloy until it is completely melted, and keep the melted state for about ten minutes, then perform the heating and melting holding process again, repeat the cycle 4-5 times to ensure the uniformity of the alloy composition; remove the alloy ingot after cooling with the furnace;

[0052] (3) Preparation of bulk amorphous alloy: Take 2 g of the alloy ingot obtained in step (2) and place it in a vacuum arc melting suction casting furnace. Adjust the vacuum degree to 5×10 -3 Pa or less, adjusting the vacuum degree and argon protective atmosphere, and adopting the copper mold suction casting method to prepare the amorphous alloy sample; wherein the prepared suction casting sample is cylindrical, with a diameter of 1.5 mm and a length of ≤40 mm;

[0053] (4) Performance testing and results

[0054] The XRD results of Hf2 amorphous alloy with a diameter of 1.5 mm show that all samples exhibit amorphous characteristics, such as Figure 1 As shown, its crystallization temperature is 828K, such as Figure 2 As shown in Table 1, its room temperature compressive mechanical properties and Vickers hardness values ​​are 4795±20GPa and 1228±13HV respectively. 0.3 ,like Figure 2 , 3 As shown in Table 1, the corrosion resistance is significantly improved compared with ordinary stainless steel. Figure 4 As shown in Table 2; it can be seen that the amorphous characteristics, room temperature compression mechanical properties, Vickers hardness and corrosion resistance of the iron-based amorphous alloy Hf2 obtained by the method of the embodiment are significantly enhanced compared with the existing ones. Therefore, the scheme of this embodiment significantly enhances the amorphous characteristics, mechanical properties, corrosion resistance and thermal stability of the iron-based amorphous alloy by replacing rare earth elements with trace alloying elements, which provides theoretical guidance for improving the amorphous forming ability and performance of iron-based amorphous alloys in the future. At the same time, it has broad application prospects in the field of metal corrosion protection and amorphous coatings, and solves the problem that the prior art has a negative correlation between de-rare earthing and amorphous alloy forming ability, resulting in the amorphous alloy system usually containing rare earth element Y, which leads to the shortcomings of complex preparation process, high cost and environmental unfriendliness.

[0055] Embodiment 5:

[0056] Take the iron-based amorphous alloy Mn2 and its preparation method as an example;

[0057] (1) Ingredients: According to the chemical formula of FeaCobCrcModCeBfMn2, metals Fe, Co, Cr, Mo, C, B, and Mn with a purity of more than 99.5% are used as raw materials for weighing and mixing. Before weighing, the oxide film on the surface of each metal raw material is first polished with coarse sandpaper, then ultrasonically cleaned with industrial alcohol, and finally dried with a hair dryer for use;

[0058] (2) Vacuum arc furnace melting: The raw materials obtained in step (1) are placed in a vacuum arc melting furnace and the vacuum degree is adjusted to 5×10 -3 Pa, using argon (pressure 0.05MPa) as a protective atmosphere, slowly heat the alloy until it is completely melted, and keep the melted state for about ten minutes, then perform the heating and melting holding process again, repeat the cycle 4-5 times to ensure the uniformity of the alloy composition; take out the alloy ingot after cooling with the furnace;

[0059] (3) Preparation of bulk amorphous alloy: Take 2 g of the alloy ingot obtained in step (2) and place it in a vacuum arc melting suction casting furnace. Adjust the vacuum degree to 5×10 -3 Pa, the vacuum degree and argon protective atmosphere were adjusted, and the amorphous alloy samples were prepared by copper mold suction casting method; wherein the prepared suction casting samples were cylindrical with a diameter of 1.5 mm and a length of ≤40 mm.

[0060] (4) Performance testing and results

[0061] The XRD results of Mn2 amorphous alloy with a diameter of 1.5 mm show that all samples exhibit amorphous characteristics (such as Figure 1 The crystallization temperature is 841K (see Figure 2 and Table 1), its room temperature compressive mechanical properties and Vickers hardness values ​​are 4874±10GPa and 1323±13HV 0.3 (See Figure 2 , 3 and Table 1), the corrosion resistance is significantly improved compared to ordinary stainless steel (see Figure 4and Table 2); It can be seen that the amorphous characteristics, room temperature compression mechanical properties, Vickers hardness and corrosion resistance of the iron-based amorphous alloy Mn2 obtained by the method of the embodiment are significantly enhanced compared with the existing ones. Therefore, the scheme of this embodiment significantly enhances the amorphous characteristics, mechanical properties, corrosion resistance and thermal stability of the iron-based amorphous alloy by replacing rare earth elements with trace alloying elements, which provides theoretical guidance for improving the amorphous forming ability and performance of iron-based amorphous alloys in the future. At the same time, it has broad application prospects in the field of metal corrosion protection and amorphous coatings, and solves the problem that the prior art usually contains rare earth element Y in the amorphous alloy system due to the negative correlation between the removal of rare earth and the formation ability of amorphous alloys, which leads to the shortcomings of complex preparation process, high cost and environmental unfriendliness.

[0062] Embodiment 6:

[0063] Take the iron-based amorphous alloy Zr2 and its preparation method as an example;

[0064] (1) Ingredients: According to the chemical formula of FeaCobCrcModCeBfZr2, metals Fe, Co, Cr, Mo, C, B, and Zr with a purity of more than 99.5% are used as raw materials for weighing and mixing. Before weighing, the oxide film on the surface of each metal raw material is first polished with coarse sandpaper to remove it, then ultrasonically cleaned with industrial alcohol, and finally dried with a hair dryer for use;

[0065] (2) Vacuum arc furnace melting: The raw materials obtained in step (1) are placed in a vacuum arc melting furnace and the vacuum degree is adjusted to 5×10 -3 Pa, using argon (pressure 0.05MPa) as a protective atmosphere, slowly heat the alloy until it is completely melted, and keep the melted state for about ten minutes, then perform the heating and melting holding process again, repeat the cycle 4-5 times to ensure the uniformity of the alloy composition; remove the alloy ingot after cooling with the furnace;

[0066] (3) Preparation of bulk amorphous alloy: Take 2 g of the alloy ingot obtained in step (2) and place it in a vacuum arc melting suction casting furnace. Adjust the vacuum degree to 5×10 -3 Pa, the vacuum degree and argon protective atmosphere were adjusted, and the amorphous alloy samples were prepared by copper mold suction casting method; wherein the prepared suction casting samples were cylindrical with a diameter of 1.5 mm and a length of ≤40 mm.

[0067] (4) Performance testing and results

[0068] XRD results of Zr2 amorphous alloy with a diameter of 1.5 mm show that all samples exhibit amorphous characteristics (see Figure 1 ), whose crystallization temperature is 823K (see Figure 2and Table 1), its room temperature compressive mechanical properties and Vickers hardness values ​​are 4516±15GPa and 1208±14HV 0.3 (See Figure 2 , 3 and Table 1), the corrosion resistance is significantly improved compared to ordinary stainless steel (see Figure 4 and Table 2); It can be seen that the amorphous characteristics, room temperature compression mechanical properties, Vickers hardness and corrosion resistance of the iron-based amorphous alloy Zr2 obtained by the method of the embodiment are significantly enhanced compared with the existing ones. Therefore, the scheme of this embodiment significantly enhances the amorphous characteristics, mechanical properties, corrosion resistance and thermal stability of the iron-based amorphous alloy by replacing rare earth elements with trace alloying elements, which provides theoretical guidance for improving the amorphous forming ability and performance of iron-based amorphous alloys in the future. At the same time, it has broad application prospects in the field of metal corrosion protection and amorphous coatings, and solves the problem that the prior art usually contains rare earth elements Y in the amorphous alloy system due to the negative correlation between de-rare earthing and amorphous alloy forming ability, which leads to the shortcomings of complex preparation process, high cost and environmental unfriendliness.

[0069] It can be seen from the analysis of the above embodiments 3-6 that after adopting the technical solution of the present application, the present invention has the following advantages:

[0070] 1. The XRD results of FeaCobCrcModCeBfM2 amorphous alloy with a diameter of 1.5 mm in the present invention show that all samples exhibit amorphous characteristics (see Figure 1 ).

[0071] 2. The FeaCobCrcModCeBfM2 bulk amorphous alloy of the present invention has high thermal stability (see Figure 2 and Table 1). Its glass transition temperature (Tg), crystallization temperature (Tx), melting temperature (Tm) and liquidus temperature (Tl) are between 823-848K, 870-891K, 1385-1393K and 1435-1454K, respectively, indicating that the alloy has good thermal stability. Table 2 shows the thermal stability properties of FeaCobCrcModCeBfM2 bulk amorphous alloy.

[0072] 3. The FeaCobCrcModCeBfM2 bulk amorphous alloy of the present invention has excellent microhardness and compressive strength (see Figure 2 , 3 and Table 1); Table 1 shows the hardness values ​​(HV 0.3 ) and compressive strength values ​​(MPa), multiple shear bands and flaky areas were observed on the surface of the specimen (see Figure 5 ), which is a typical fracture feature of brittle amorphous alloys.

[0073] 4. The FeaCobCrcModCeBfM2 bulk amorphous alloy of the present invention has excellent corrosion resistance (see Figure 4 and Table 2); the self-corrosion potential and self-corrosion current density of FeaCobCrcModCeBfM2 bulk amorphous alloy in 3.5w% NaCl solution are better than those of stainless steel.

[0074] In addition, the mechanical properties and corrosion resistance of the four prepared Fe-based amorphous alloys were compared, as shown in Figure 2. Figure 3 and Figure 4 As shown, the hardness value and compressive strength of the iron-based amorphous alloy of Mn2 alloy are the highest, and the corrosion resistance of the iron-based amorphous alloy of Zr2 alloy is the best. The application of the present invention focuses on corrosion resistance, so FeaCobCrcModCeBfZr2 is selected as the component formula with the best ratio of the present invention.

[0075]

[0076] Table 1 Thermal properties and mechanical properties of Fe-based amorphous alloys

[0077]

[0078] Table 2 Electrochemical parameters

[0079] The above is only an embodiment of the present invention, and the common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several improvements can be made without departing from the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of the claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A microalloyed high corrosion resistant iron-based amorphous alloy, characterized in that: Its chemical formula is Fe a Co b Cr c Mo d C e B f M2, wherein M is a microalloying element, specifically one of Mo, Hf, Mn and Zr, and the content of each element is expressed in atomic percentage (at.%), as follows: a is 41-45, b is 5-9, c is 13-17, d is 10-14, e is 13-17, f is 4-8, and a+b+c+d+e+f=98.

2. The microalloyed high corrosion resistant iron-based amorphous alloy according to claim 1, characterized in that: The specific chemical formula of the iron-based amorphous alloy is: Fe a Co b Cr c Mo d C e B f Zr2.

3. A method for preparing a microalloyed high corrosion resistant iron-based amorphous alloy, characterized in that: The following steps are involved: Step 1: According to the chemical formula Fe a Co b Cr c Mo d C e B f M2 weighs the ingredients; Step 2: Place the ingredients obtained in step 1 into a vacuum arc melting furnace, adjust the vacuum degree to below Pa, and use argon as a protective atmosphere with an argon pressure of 0.05 MPa; heat and melt the ingredients, cool them in the furnace, and then take out the alloy ingot; Step 3: Take 1.5-2.5 g of the alloy ingot obtained in step 2 and put it into a vacuum arc melting suction casting furnace, then adjust the vacuum degree to below Pa, use argon as a protective atmosphere, and the argon pressure is 0.05 MPa. After the alloy ingot is heated and melted, it is quickly cooled by suction casting and cast to obtain an amorphous alloy.

4. The method for preparing a microalloyed high corrosion resistant iron-based amorphous alloy according to claim 3, characterized in that: In step 2, the raw material is heated slowly until it is molten, and then kept in the molten state for 9-11 minutes, and then the heating and melting holding process is performed again, and the cycle is repeated 4-5 times to ensure that an alloy ingot with uniform composition is obtained.

5. The method for preparing a microalloyed high corrosion resistant iron-based amorphous alloy according to claim 3, characterized in that: In step three, the amorphous alloy is cast into a cylindrical shape with a diameter of 1.4-1.6 mm and a length of ≤40 mm.

6. The method for preparing a microalloyed high corrosion resistant iron-based amorphous alloy according to claim 3, characterized in that: In step one, the purity of the raw materials of each ingredient is above 99.5%, and before step one, the oxide film on the surface of each metal raw material is removed by grinding with coarse sandpaper, then ultrasonically cleaned with industrial alcohol, and finally dried with a hair dryer for use.

Citation Information

Patent Citations

  • Iron-base bulk amorphous alloy with high glass-forming ability

    CN1603445A